If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3a-4=3(2a+1)+5
We simplify the equation to the form, which is simple to understand
3a-4=3(2a+1)+5
Reorder the terms in parentheses
3a-4=+(+6a+3)+5
Remove unnecessary parentheses
+3a-4=+6a+3+5
We move all terms containing a to the left and all other terms to the right.
+3a-6a=+3+5+4
We simplify left and right side of the equation.
-3a=+12
We divide both sides of the equation by -3 to get a.
a=-4
| 7X^3-14x^2=0 | | 2x-25=x | | -(x+4)-2(1+x)=x | | 8t^2+14t+10=0 | | 9-9a=2-10a | | -30(6x-12)=4-16x | | 309/6 | | 2/3(x+5)=1/4(5x-3) | | b=2/3(h-1) | | 4.11x+5=6.6+3.71x | | y/16+8=4 | | (4n-3n^3)-(3n^3-4n)= | | 7+2(x+1)=9+2x | | x^2+10x=250 | | 1-4x=3x+16 | | 12n^2+8n^3+6n= | | 10.6-9.6z+3.8=2.9 | | (a-4)/2-(5(a-4))/8=(5a+20)/4 | | -7=x/5 | | 4x+1+3x+2+2x+3+x+4=10x+10 | | (13x-8)+58=180 | | 16-4x=x+11 | | -3x-8=21 | | 40/n=8/5 | | x^2+200x+12500=0 | | 0,4x-2/3=x/5+1 | | 11.4/19 | | 5[1-2w]+8w=15 | | -6(a+9)+7=3a+2(4a-1) | | -10n+12n=n+2 | | 18x1/6 | | 13a+2=6(a-2) |